If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + 9b = 0 Solving 6a + 9b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9b' to each side of the equation. 6a + 9b + -9b = 0 + -9b Combine like terms: 9b + -9b = 0 6a + 0 = 0 + -9b 6a = 0 + -9b Remove the zero: 6a = -9b Divide each side by '6'. a = -1.5b Simplifying a = -1.5b
| 7.3x-3.1=11.5 | | 5t^2-15+2=10 | | 8a+3b= | | X^2+2x=60 | | 7x+5(x+2)+4= | | 3p+5=30p | | 4(logx-1)=18 | | 16x^4+16x^2+3=0 | | 12a+15b= | | (7x-4)(7x+5)= | | 3v+w+8-2v+2= | | -2-17-22=2y+3(y-6) | | -5+(19)+(-34)+44= | | 2x+5x^4+6=0 | | 8(4x+4)= | | -6(x+3)+2x+6=8x+7 | | 20*7-4*7= | | -16t^2+144t-160=0 | | 15w+21=3(5w-7) | | -5+200=100 | | 3y^2-6y-24= | | -3+3(z-2)=(-7z+3)-6 | | 3x=cos(0.5x) | | 18=6v | | 4u-7u=-1-14 | | 5(-3-6n)=195 | | 4x^2-4x-48= | | (x+4)(xy-6)=7x | | 16x^2+-40x+25=0 | | 5/2*4-10/5+6= | | 16x-40x+25=0 | | 5x^3-20x= |